Lignin-first biorefinery of corn stalk via zirconium(IV) chloride/sodium hydroxide-catalyzed aerobic oxidation to produce phenolic carbonyls. (June 2022) - Liu, Chao; Lin, Fei; Kong, Xiangchen; Fan, Yuyang; Xu, Weicong; Lei, Ming; Xiao, Rui
Graphical abstract: Highlights: ZrCl4 /NaOH-catalyzed lignin-first oxidation of corn stalk was achieved. Yields of phenolic monomers was up to 13.2 wt% via lignin-first oxidation. Phenolic carbonyls were the dominated products with high selectivity of 93%. Cellulose-rich residues proved the fragmentation and dissolution of lignin streams. Abstract: Lignin-first biorefinery of corn stalk via ZrCl4 /NaOH-catalyzed aerobic oxidation for phenolic carbonyls production was reported. Under the co-catalysis of ZrCl4 and NaOH, lignin in corn stalk was oxidized into phenolic aldehydes ( p -hydroxybenzaldehyde, vanillin, and syringaldehyde), ketones ( p -hydroxyacetophenone, acetovanillone, and acetosyringone), acids ( p -hydroxybenzoic acid and vanillic acid), and other derivatives. Reaction conditions, including time, temperature, ZrCl4 dosage, NaOH dosage, MeCN/H2 O ratio, and initial O2 pressure were comprehensively screened, and the optimal lignin-derived monomer yields of 13.2 wt% was obtained. Among these aromatic compounds, phenolic aldehydes were the main products, and the overall selectivity of phenolic carbonyls was as high as 93%. Cellulose-rich residues after lignin-first oxidation were further characterized by thermogravimetry and analytical pyrolysis with corn stalk as the control, proving the good fragmentation and dissolution of lignin streams. In general, ZrCl4 /NaOH-catalyzed lignin-first oxidation provided a novel approach for lignin valorization, and achieved the highest reported phenolic carbonyls selectivity.